European Monetary Union: Nominal convergence, real divergence and slow growth? An investigation into the effects of changing macroeconomic policy institutions associated with monetary union - Eckhard Hein; Achim Truger (Hans-Böckler-Stiftung, Wirtschafts- und Sozialwissenschaftliches Institut (WSI), 2002)
It is by now widely accepted that the structural characteristics of the countries to become the euro area did not adhere to the conditions of an optimum currency area (OCA) when the euro was introduced in 1999. However, the satisfaction of OCA criteria may not be required for a workable currency union, because the criteria have to rely on a very restrictive concept of money and their satisfaction may be largely endogenous to shifts in the economic policy regime. Growth and convergence of prosperity across a currency union rather depend on the appropriate macroeconomic policy institutions. Therefore, in this paper the effects of the new EMU institutional framework for monetary, fiscal and wage policies on overall growth and on convergence across the euro area are analysed. It is concluded that not only the period of nominal convergence towards EMU but also the initial period of the euro area has suffered from a rather restrictive macroeconomic policy mix which has neither been conducive to aggregate growth nor to real convergence across the euro area. In order to improve growth and convergence some major institutional reforms seem to be required.
Keywords: E58; E61; F15; 330; European Monetary Union; nominal convergence; real convergence; macroeconomic policy mix; Europäische Wirtschafts- und Währungsunion; Policy-Mix; Entwicklungskonvergenz; Wirtschaftswachstum; Internationale wirtschaftspolitische Koordination; EU-Staaten; Makroökonomischer Einfluss